Association Between Stress Levels and Waist Circumference Among Medical and Health Sciences Students at Universitas Muhammadiyah Sumatera Utara - Windy Nabila Royana Harahap; Fitri Nur Malini Siregar; Nanda Sari Nurlita; Irfan Darfika Lubis (Jurnal Kesehatan dan Kedokteran, 2026)
Stress may influence physiological balance through hormonal mechanisms, particularly increased cortisol levels, which are associated with visceral fat accumulation in the abdominal area. Waist circumference is an important anthropometric indicator for assessing central obesity and cardiometabolic risk. Medical students are vulnerable to stress due to high academic demands, which may affect their health status. Objective: This study aimed to determine the association between stress levels and waist circumference among students of the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara. Methods: This observational analytic study used a cross-sectional design. A total of 89 students from the 2022–2024 cohorts were selected using quota sampling based on the inclusion criteria. Stress levels were measured using the Depression Anxiety Stress Scale-42 (DASS-42), while waist circumference was measured using a flexible measuring tape according to standard anthropometric procedures. Data were analyzed using an exact statistical test with a significance level of 0.05. Findings: The results showed a statistically significant association between stress levels and waist circumference, with a p-value of 0.011. Students with higher stress levels tended to have a greater proportion of central obesity compared to those with normal stress levels. Implication: These findings highlight the importance of stress management and healthy lifestyle promotion in student health programs. Originality: This study provides empirical evidence on the relationship between psychological stress and waist circumference among medical students in the Indonesian university context.